Screening of soil actinomyectes against Salmonella serovar Typhi NCTC 5761 and characterization of the prominent active strains - Goljanian Tabrizi, Sanaz (Iran J Microbiol, 2013)
BACKGROUND AND OBJECTIVES: Annual incidence of infection with S. Typhi is estimated to be about 17 million cases worldwide. A systematic search among actinomycete isolates from soil of Iran aimed at finding active actinomycetes against the causative agent of typhoid fever, Salmonella Typhi was carried out during this study. MATERIALS AND METHODS: Our anti-Salmonella screening program resulted in nine highly active actinomycete isolates. All nine antibiotic producing strains showed broad-spectrum antibacterial activity, as five strains showed antifungal activity as well. Based on microscopic morphology and cell wall analysis, all nine active actinomycete strains were representatives of the genus Streptomyces. Three of the producing strains including the isolates HG87, HG116 and HG443 with inhibition zone of >20 mm, were selected for further identification and investigation of cytotoxic effects. RESULTS AND CONCLUSION: None of the producing strains showed cytotoxicity on HEK and USSC cell lines, while strain HG116 showed excellent antitumor activity on T47D cancer cell lines. Isolates HG87, HG116 and HG443 can be distinguished from the related species by some phenotypic and biochemical characteristics. Our results demonstrate the broad-range biological activity exhibited by bioactive compounds of soil actinomycetes from Iran.